No caminho da sua morte eu estarei: compreendendo a rede de apoio de pessoas idosas em cuidados paliativos - Silva, Charles Vieira da (2023)
With population aging, chronic pathologies and their consequences also increase, thus there is a need to think about and qualify care measures at the end of life. In this context, the importance of palliative care and the existence of social support networks for the realization of better care conditions for the elderly who experience this process is highlighted. Given this scenario, the objective of this research is to know the social support networks of elderly people in hospitalized palliative care and to identify the experiences lived by the members of these networks in the health-disease process of these elderly people. Methodologically, it is a qualitative, descriptive research, carried out through a field study with 15 elderly people who were in palliative care during the period of hospitalization, in a large hospital in the state of Rio Grande do Sul. South, as well as with 18 members of the support networks of these elderly people. The results were presented in two scientific productions: Scientific Production I, “Social support networks for elderly people hospitalized in palliative care: characteristics and experiences lived in the palliative care process”, which aimed to know the characteristics of social support networks for elderly people hospitalized in palliative care and the experiences lived by the members of these networks in the palliative process, during the period of hospitalization, making it evident that all the members indicated by the elderly as their social support network are family members, predominantly women, calling attention to the absence, in the network mapping, of public policies to support people in palliative care. The lack of understanding about the clinical picture and palliative care, the family changes resulting from the new context and the construction of bonds in the face of the proximity of death stand out in the experience of family members of the support networks. Scientific Production II, “Influences of relationships established in the world of work on the care process exercised by family members who make up the support network of hospitalized elderly people in care”, sought to identify how the relationships established in the world of work influence the process of care exercised by family members who make up the support network of elderly people hospitalized in palliative care. It was identified that the relationships in the world of work directly influence the availability of the support network for care. The feminization of care was present, highlighting the woman with the multiple roles she assumes in the sexual division of work, highlighting that of caregiver. The family support network is evidenced as the main source of social protection, held accountable through the existing familism in public policies, which contributes to family overload and vulnerability. With this, the data presented here provide evidence for the importance of implementing public policies in our country that contemplate the elderly and their support networks in the end of life process, considering them in their entirety through the physical, emotional and psychological aspects. social